D-Branes and Gauge Fields - Năstase, Horaţiu [UNESP] (My University, 2019)
In this chapter we will explore the consequences of having Dirichlet boundary conditions for open strings. It will imply the existence of objects called D-branes, that have gauge fields on their “worldvolume”.